Development of the educational dimension of ethics of research committees (ERCs) - Silva Barbosa, Adriana; Silva de Oliveira Boery, Rita Narriman; Boery, Eduardo Nagib; Ferrari, Márcio Roger (Acta Bioethica, 2012)
The importance of the educational and consulting nature of ethics of research committees (ERCs) highlights the value of research which studies these dimensions in the committees. Aims: to analyze how ERCs have carried out their educational and consulting role; to learn whether advisors have some training in research ethics; to identify whether researchers had guidance about research ethics in their academic career. This is a quantitative and descriptive study approved by CEP/UESB under protocol 134/2009, carried out with 95 informants and analyzed by Software Sphinx. According to data obtained, nearly 71.5% research participants consider educational and consulting activities carried out by ERC infrequent or lacking; 60% participants have some ethical training in their academic career. These data show that ERCs need greater institutional support and funding in order to consolidate their educational-consulting dimension.